Basic studies for the microbiological control of the potato ondean weevil ("potato white worm") (Premnotrypes vorax) with Beauveria spp. and Metarhizium sp. - TORRES-PÉREZ, ROCÍO; LÓPEZ-ÁVILA, A. (Revista Colombiana de Entomología, 1997)
The potato Andean weevil, Premnotrypes vorax, is one of the most important economic insect pests of the potato crop in Colombia. This pest severely damages 63.71% of the crop in the country, which represents losses estimated at about US 220 per hectare. This study was developed with the purpose of evaluating and comparing different isolates and doses of Beauveria bassiana, B. brongniartii and Metarhizium anisopliae for the control of the pest under laboratory and mesh house conditions and evaluate the efficiency of the control of the insect in the prevention of the crop damage. The pathogenicity of four isolates ofB. bassiana, one of B. brongniartii and four of Metarhizium anisopliae, was evaluated on full grown larvae of P vorax, selecting the ones that showed the most mortality percentage. The isolates selected were then evaluated against adults of P. vorax in the three different concentrations: 1 x105 1 x107 and 1 x109 propagules/ml, (colony forming units = conidia and mycelium) in a random experiment with 16 treatments and three repetitions. And finally, two isolates of B. bassiana (Bv3 and Bv6) were selected from here to be evaluated in an experiment in mesh house. The test was carried out with adults of the pest and plants of Solanum phureja applying the fungus in concentration of3x108 propagules/ml liquid and solid forms. In this experiment, the mortality of the insect has evaluated as well as the damage caused to the tubers. From the five isolates evaluated in the laboratory, the two of Beauveria bassiana native isolated from specimens of the pest found in the field, causing 100% of mortality of the insects. The highest percent of mortality of adults in the mesh house experiment was obtained with the liquid application form of the Bv6 isolate Bv6 with C8.5%. But the best protection of the tubers was obtained with the isolate Bv3 in the same application form, with a 62.29% of control.